Referral of patients between Primary and Secondary levels of health care in the Port Elizabeth Metropole - Odufuwa, Oluwatoyin Aliu (Stellenbosch : Stellenbosch University, 2012)
Research report (MMed) -- Interdisciplinary Health Sciences, Stellenbosch, 2010.